Records management for museums and galleries : an introduction - Brunskill, Charlotte (Chandos information professional series, 2012)
"Offers a comprehensive overview of records management work within the heritage sector and draws on over a decade of experience in applying fundamental principles and practices to the specific cirumstances of museums." BOOK JACKET.